Analisis Usahatani Intensifikasi Agrosilvopastura Di Kalurahan Wiladeg, Kapanewon Karangmojo, Kabupaten Gunungkidul, Provinsi Daerah Istimewa Yogyakarta - Muhammad Abdul Rahman Subrata; Slamet Riyanto; Wahyu Andayani; San Afri Awang; Greitta Kusuma Dewi (Faculty of Forestry Universitas Gadjah Mada, 2022)
This research aimed to analyze the increase in income from intensified agrosilvopastoral in Wiladeg Village, Karangmojo Sub-district, Gunungkidul Regency, Yogyakarta, Indonesia. This research employed Participatory Action Research (PAR) to collect data through four cycles of food crop production trials under forest stands. The on-farm trials used the submersible-well technology and lasted for three years. The Average Equivalent Value (AEV) analysis grouped the respondents into two strata based on land ownership. Stratum-1 consisted of respondents with an agrosilvopastoral area of ≤ 4000 m2, while stratum-2 of > 4000 m2. The off-farm intensification trials involved three cow fattening cycles and used Net Present Value (NPV) analysis. The results showed that on-farm trials contributed an increase in AEV, namely 692% on land strata-1 and 462% on land strata-2. The off-farm trials provided an NPV of IDR 14,679,000,00/year in the off-farm sector of cow fattening. Based on these results, intensified agrosilvopastoral was feasible to increase land productivity both on-farm and off-farm in Wiladeg Village.